Achromobacter Spp.: A retrospective review of rare and emerging pathogen - Soni Sinha; Nikhil Raj; Shipra Dobhal; Anupam Das; Jyotsna Agarwal (MGM Journal of Medical Sciences, 2023)
Background: Achromobacter spp. is a rare nosocomial pathogen known to cause many serious infections like bloodstream infection, osteomyelitis, meningitis, urinary tract infections, corneal ulceration, peritonitis, and endocarditis. Materials and Methods: In this study, we retrospectively analyzed all the bacteriological sample records from the bacteriology database from January 2021 to December 2021 to determine the prevalence of Achromobacter spp. Result: Nine patients with Achromobacter xylosoxidans causing bacterial infection were identified, from whom five blood samples, two pus, one respiratory sample, one central venous pressure (CVP), and one cerebrospinal fluid were found positive for Achromobacter spp., among whom one was a 6-year-old patient having the same organism from two different body sites—CVP line and cerebrospinal fluid. Five patients had coinfection with another organism, whereas acute kidney injury was the most common comorbidity. Conclusion: In our single-center experience, approximately 50% of the cases with Achromobacter denitrificans bacteremia suffered from chronic kidney disease and had a history of antibiotic therapy, hospitalization, and the presence of devices. Active research on rising trends of Achromobacter spp. needs to be promoted.